Tymcza, narka, bezva, senza – procesy skracania w czeszczyźnie i polszczyźnie mówionej - KRAWCZYK, Katarzyna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2009)
Artykuł traktuje o procesach skracania w języku czeskim i polskim. Materiał egzemplifikacyjny pochodzi w znacznej mierze z języka młodzieży czeskiej i polskiej, ponieważ tę grupę społeczną uważa się za najbardziej kreatywną grupę użytkowników języka, przy czym zwraca się uwagę na fakt, że w języku czeskim skrótowce występują również w języku mówionym dorosłych Czechów częściej, niż ma to miejsce na gruncie polszczyzny. Autorka zauważa także panującą w obu językach tendencję do skracania słów pochodzenia angielskiego m.in. na drodze procesów derywacyjno-abrewiacyjnych, np. net < internet, noťas < notebook itd.

The article describes the processes of shortening in Polish and in Czech. The exemplificative material is mostly derived from the Polish and Czech teenage language, because this social group is treated as the most creative group of language users, although it is significant to point out, that in Czech, acronyms can be found in spoken language of adults more often than in the Polish language. The author also notices the tendency to shorten words of English origin among other things, due to the derivative-abbreviatory processes, for example: net < internet, noťas < notebook etc.
Tymcza, narka, bezva, senza – processes of shortening in the Polish and Czech spoken language
Keywords: Czeski język potoczny; Czech spoken language; Polski język potoczny; Polish spoken language; Tendencje skracania wyrazów; Tendency to shorten words; Procesy derywacyjno-abrewiacyjne; Derivative-abbreviatory processes